1994
DOI: 10.1093/hmg/3.8.1217
|View full text |Cite
|
Sign up to set email alerts
|

Identity-by-descent and association mapping of a recessive gene for Hirschsprung disease on human chromosome 13q22

Abstract: Hirschsprung disease (HSCR) is a congenital disorder of unknown etiology characterized by the absence of enteric ganglia in the distal colon. We have ascertained a large, inbred, Mennonite kindred which demonstrates a high incidence of Hirschsprung disease (HSCR). Genealogical analysis of all kinship relationships identified a single common ancestral couple for all parents of affected offspring. Segregation analysis yielded a segregation ratio of 10.67% for males and 5.45% for females. We searched for location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(116 citation statements)
references
References 0 publications
2
111
0
3
Order By: Relevance
“…This demonstrated that shared segment mapping can be used to assign a gene by using only a limited number of markers, whenever a suitable population is available. The same principle has been used for the mapping of other monogenic disorders too, in both humans (Puffenberger et al 1994;Carlton et al 1995;Kalaydjieva et al 1996;Newport et al 1996) and cattle (Charlier et al 1996). Byler disease, a form of PFIC, was mapped to the BRIC region on chromosome 18q21, by studying two distantly related patients, both descendants of Jacob Byler (Carlton et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that shared segment mapping can be used to assign a gene by using only a limited number of markers, whenever a suitable population is available. The same principle has been used for the mapping of other monogenic disorders too, in both humans (Puffenberger et al 1994;Carlton et al 1995;Kalaydjieva et al 1996;Newport et al 1996) and cattle (Charlier et al 1996). Byler disease, a form of PFIC, was mapped to the BRIC region on chromosome 18q21, by studying two distantly related patients, both descendants of Jacob Byler (Carlton et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…For many species, however, the lack of a genomic map leads to an inability to separate background LD from other types of LD. Furthermore, events other than admixture, such as population bottlenecks (Lynch and Walsh, 1998) or important demographic changes, could also generate strong LD and increase the occurrence of background LD (Jorde, 2000;Peltonen, 2000;Puffenberger et al, 1994). In this situation, users should not rely on the genomic map alone to decide which loci to use or not.…”
Section: Introductionmentioning
confidence: 99%
“…35 Puffenberger et al 35 ascertained a large, inbred, Mennonite pedigree (depicted in Figure 1 in Puffenberger et al 35 ), exhibiting high incidence of Hirschsprung disease. Genealogical analysis of all members of the Mennonite pedigree identified a single common ancestral couple for all parents of the affected offspring.…”
Section: Chromosome Segment Sharing O Libiger and Nj Schorkmentioning
confidence: 99%
“…Figure 2 The probability of sharing a 10 Mb IBD segment when IBS sharing is observed with markers 2 Mb apart (chromosome 13). The conditional probability that affected members of the Mennonite pedigree (depicted in Figure 1 in Puffenberger et al 35 ) share a 10 Mb IBD segment on chromosome 13 (ie, five markers), given the observed IBS sharing. The solid lines correspond to IBS sharing using five markers in linkage equilibrium with five equifrequent alleles (full black line), vs one common allele with frequency equal to 0.6 and four rare alleles with frequency equal to 0.1 (full gray line).…”
Section: Chromosome Segment Sharing O Libiger and Nj Schorkmentioning
confidence: 99%